2005
DOI: 10.1091/mbc.e05-04-0347
|View full text |Cite
|
Sign up to set email alerts
|

ATP Production inChlamydomonas reinhardtiiFlagella by Glycolytic Enzymes

Abstract: Eukaryotic cilia and flagella are long, thin organelles, and diffusion from the cytoplasm may not be able to support the high ATP concentrations needed for dynein motor activity. We discovered enzyme activities in the Chlamydomonas reinhardtii flagellum that catalyze three steps of the lower half of glycolysis (phosphoglycerate mutase, enolase, and pyruvate kinase). These enzymes can generate one ATP molecule for every substrate molecule consumed. Flagellar fractionation shows that enolase is at least partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 61 publications
4
110
2
Order By: Relevance
“…13 for the chloroplast proteome) and are unable to grow on sucrose or glucose as a sole carbon source (1). In the cytosol, the enzymes downstream of glyceraldehyde 3-phosphate are concentrated where the glycolytic ATP production is most needed, the flagella (14).…”
mentioning
confidence: 99%
“…13 for the chloroplast proteome) and are unable to grow on sucrose or glucose as a sole carbon source (1). In the cytosol, the enzymes downstream of glyceraldehyde 3-phosphate are concentrated where the glycolytic ATP production is most needed, the flagella (14).…”
mentioning
confidence: 99%
“…the outer segments of mammalian photoreceptor cells 63 ). Mammalian sperm-specific isoforms of glycolytic enzymes such as glyceraldehyde 3-phosphate dehydrogenase 64 and enolase 65 have likely evolved recently, as the glycolytic enzymes identified in Chlamydomonas flagella 66 are not closely related and appear to have been targeted for flagellar use specifically in algae. Completely different methods of flagellar ATP generation occur in other organisms, including phosphocreatine/creatine phosphokinase shuttles in sea urchin 67 and mammalian 68 spermatozoa, and in chicken photoreceptor outer segments 69 , and a phosphoarginine/arginine phosphokinase shuttle in Paramecium cilia 70 .…”
Section: Diversification Of Flagellar Structure and Function During Ementioning
confidence: 99%
“…17 For example it has been demonstrated that the high amount of ATP required in Chlamydomonas for flagella motility is supported by the presence of enolase in the flagellar microtubular compartment. 21 Moreover, alpha-enolase was identified as having a positive relationship with the first cycle conception rate in stallions. 22 In infertile men, sperm-specific enolase enzyme activity was elevated in normal sperm compared to abnormal sperm.…”
Section: View Article Onlinementioning
confidence: 99%